Molecular dynamics studies show solvation structure of type III antifreeze protein is disrupted at low pH. (April 2018) - Peramo, Antonio
Graphical abstract: Highlights: MD simulations with the antifreeze protein 1KDF show disruption in water solvation at pH1. Water density distributions affected the basal surface residues but not ice the binding surface residues. Changes were induced by a small disruption in the secondary structure propensities of some titrable residues, i.e. GLU35. Results may explain the experimentally observed reduction in antifreeze activity previously reported for 1KDF at pH1. Abstract: Antifreeze proteins are a class of biological molecules of interest in many research and industrial applications due to their highly specialized function, but there is little information of their stability and properties under varied pH derived from computational studies. To gain novel insights in this area, we conducted molecular dynamics (MD) simulations with the antifreeze protein 1KDF at varied temperatures and pH. Water solvation and H-bond formation around specific residues – ASN14, THR18 and GLN44 – involved in its antifreeze activity were extensively studied. We found that at pH1 there was a disruption in water solvation around the basal and the ice binding surfaces of the molecule. This was induced by a small change in the secondary structure propensities of some titrable residues, particularly GLU35. This change explains the experimentally observed reduction in antifreeze activity previously reported for this protein at pH1. We also found that THR18 showed extremely low H-bond formation, and that the three antifreeze residues all had very low average H-bond lifetimes. Our results confirm long-standing assumptions that these small, compact molecules can maintain their antifreeze activity in a wide range of pH, while demonstrating the mechanism that may reduce antifreeze activity at low pH. This aspect is useful when considering industrial and commercial use of antifreeze proteins subject to extreme pH environments, in particular in food industrial applications.